The genus Gasteruption Latreille, 1796 (Hymenoptera: Gasteruptiidae) in the Czech Republic and Slovakia: distribution, checklist, ecology, and conservation status - Bogusch, Petr (Zootaxa, 2021)
The genus Gasteruption (Gasteruptiidae) is represented in Europe by more than 30 species. Of these, twenty-one are recorded from the Czech Republic and Slovakia, with six being new records for the Czech Republic and eight for Slovakia. Three species are recorded as new for Bohemia (western part of the Czech Republic). Gasteruption goberti is excluded from the fauna of the Czech Republic because specimens previously identified as G. goberti belong to G. caucasicum. Four species (G. assectator, G. caucasicum, G. jaculator and G. nigritarse) are common and widespread in both countries, G. tournieri is very common but prefers warmer regions. Only G, subtile occurs predominantly in higher altitudes of mountain ranges, while the other species are usually restricted to or are more common in warmer regions. Gasteruption opacum and G. subtile are regionally extinct from the Czech Republic and G. paternum from Slovakia, with the the most recent records of these species are pre-1990. Gasteruption freyi, G. hastator and G. hungaricum are considered very endangered thermophilous species of loess walls and steppe habitats with a marked loss of occurrence records post-1990. Locally common but much rarer than in the past are G. erythrostomum and G. boreale. Due to the fact that recent determination keys are focused on other regions, a determination key for all species recorded in central Europe is presented.